Response and growth of some maize varieties (Zea mays L.) at various KNO3 concentrations - Raspowo Hadikusumo Diarjo; Muhammad Farid Badaruddin; Ambo Ala; Sunanto Sunanto; Ahrani Akbar Fachri (Jurnal Agercolere, 2022)
This study aimed to determine the interaction effects of several maize varieties and KNO3 concentrations on maize production. The research was carried out from December 2020 to April 2021 at the Indonesian Cereal Research Institute Facility, Bajeng District, Gowa Regency, South Sulawesi (5°18'21.5"S, 119°28'38.6"E). The study was designed using a split-plot experimental design, where the main plot was variety (V) which consisted of 4 varieties V1 (NASA-29), V2 (JH-37), V3 (BISI-2), and V4 (Pioner P-35). The subplots were KNO3 (K) concentration which consisted of 4 concentrations, namely Control (K0), 2.5 g.L–1 (K1), 5 g.L–1 (K2), and 7.5 g.L–1 (K3). Observational data were processed using ANOVA, and if there was a significant difference in the treatment, it was further tested with a 0.05 LSD follow-up test. The results showed that the JH-37 variety gave the best response, such as plant height, cob length, and production. The 7.5 g.L–1 KNO3 concentration gave the highest effect on all parameters of maize production; The interaction between the JH-37 variety with 7.5 g.L–1 KNO3 concentration gave the highest maize production; Parameters that have a positive correlation with maize productivity are expressed by plant height and weight of 1000 seeds.